2017
DOI: 10.4103/jispcd.jispcd_284_17
|View full text |Cite
|
Sign up to set email alerts
|

Platelets and their pathways in dentistry: Systematic review

Abstract: Advancing research in medicine and technology has benefitted the mankind immensely with its contribution toward an improved life quality and increased life expectancy. The inability of a human body to autoregenerate has resulted in an increased demand for newer and healthier tissues and organs. Therefore, the restoration of naturally replicated tissue components has become a subject of interest for the scientific community lately. There was felt an intense quest for promoting strategies that could restore tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Progress in medicine in general has also led to rapid advances in platelet application. In 1972, for the first time, Matras used platelets as sealants to establish blood homeostasis during surgical procedures 14 . Furthermore, in 1975 Oon and Hobbs were the first scientists to use PRP in reconstructive treatment 15 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Progress in medicine in general has also led to rapid advances in platelet application. In 1972, for the first time, Matras used platelets as sealants to establish blood homeostasis during surgical procedures 14 . Furthermore, in 1975 Oon and Hobbs were the first scientists to use PRP in reconstructive treatment 15 .…”
Section: Resultsmentioning
confidence: 99%
“…In 1972, for the first time, Matras used platelets as sealants to establish blood homeostasis during surgical procedures. 14 Furthermore, in 1975 Oon and Hobbs were the first scientists to use PRP in reconstructive treatment. 15 In 1987, Ferrari et al used platelet‐rich plasma in heart surgery as an autologous source of transfusion for the first time, thus reducing intraoperative blood loss, hematological disorders of the peripheral pulmonary circulation, and subsequent use of blood products.…”
Section: Resultsmentioning
confidence: 99%
“…Platelets also play a critical role in repairing bone fractures [ 30 ]. Previous studies on the supportive effects of platelets on bone formation have shown that PDGF induces bone formation by influencing cell proliferation, chemotactic differentiation, and extracellular matrix synthesis [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…These PGFs join to specific target tyrosine growth factor receptors, which then activate intracellular signal transduction pathways [11,12]. Several preclinical and clinical studies highlighted the supportive effect of PLTs on bone formation showing that platelet-derived growth factors (PDGFs) favor bone formation by affecting cell proliferation, chemotaxis differentiation, and extracellular matrix synthesis [13,14]. On the other hand, preclinical in vitro studies showed the role of PLTs in osteoclastogenesis and bone resorption, but the exact mechanism has not been yet proposed [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Several preclinical and clinical studies highlighted the supportive effect of PLTs on bone formation showing that platelet-derived growth factors (PDGFs) favor bone formation by affecting cell proliferation, chemotaxis differentiation, and extracellular matrix synthesis [13,14]. On the other hand, preclinical in vitro studies showed the role of PLTs in osteoclastogenesis and bone resorption, but the exact mechanism has not been yet proposed [13,14]. These unique biological properties of PLTs emphasize why their derivatives were increasingly used in the clinical scenario to support the healing process in different pathological conditions, including musculoskeletal diseases [15][16][17].…”
Section: Introductionmentioning
confidence: 99%